2020
DOI: 10.1155/2020/1927017
|View full text |Cite
|
Sign up to set email alerts
|

Amaranthus mangostanus Inhibits the Differentiation of Osteoclasts and Prevents Ovariectomy‐Induced Bone Loss

Abstract: Bone homeostasis is dynamically balanced between bone forming osteoblasts and bone resorbing osteoclasts. Osteoclasts play an important role in bone destruction and osteoporosis, and they are derived from monocyte/macrophages in response to macrophage colony-stimulating factor (M-CSF) and receptor activator of nuclear factor κB (NF-κB) ligand (RANKL). Amaranthus mangostanus L. (AM) is a plant with powerful antioxidant and other biological activities including anti-inflammatory, antidiabetic, and antihyperlipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…Additionally, PD98059 rescued osteoclastogenic suppression effect of trehalose, indicating that ERK1/2 phosphorylation reduced bone resorption. Several studies demonstrated that ERK regulates OC differentiation, 49,50 which was consistent with the results of the present study. Moreover, HCQ markedly increased the p-ERK levels, indicating an association between autophagosomes and ERK1/2 phosphorylation.…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, PD98059 rescued osteoclastogenic suppression effect of trehalose, indicating that ERK1/2 phosphorylation reduced bone resorption. Several studies demonstrated that ERK regulates OC differentiation, 49,50 which was consistent with the results of the present study. Moreover, HCQ markedly increased the p-ERK levels, indicating an association between autophagosomes and ERK1/2 phosphorylation.…”
Section: Discussionsupporting
confidence: 93%
“…The relative quantification was normalized against the level of glyceraldehyde 3-phosphate dehydrogenase (GAPDH). The relative transcript expression was calculated using the 2 −DCT method, and results were expressed as folds of change relative to the expression in the control group [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Hit 4 is the ethanol extract from Amaranthus spinosus , a widely available food plant in Taiwan and tropical countries. Furthermore, the ethanol extract of Amaranthus mangostanus has been demonstrated to prevent ovariectomy-induced bone loss in mice ( 22 ). Thus, it was selected for further validation and analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The compounds identified by this approach may have applications as therapeutics for FGFR3-associated cancers and skeletal dysplasias. JCI Insight 2023;8 (22):e171257 https://doi.org/10.1172/jci.insight.171257 in U2OS cells (Figure 1E). Notably, U2OS cells coexpressing both SH2(SH2B)/GFP and different forms of FGFR3 (WT, ACH, and TDI) displayed distinct intracellular punctate GFP signals (Figure 1F).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation